Effects of beef cow milk production levels on longevity and stayability - Culbertson, Miranda M., author; Enns, R. Mark, advisor; Thomas, Milton G., committee member; Pritchett, James, committee member (Colorado State University. Libraries, 2014)
The objective of this study was to determine the effects of beef cow milk potential on their ability to remain in the herd. We hypothesized that in areas with more arid climates and associated forage quantity and quality challenges, cows with higher genetic potential for milk production, measured as milk EPD, may not remain in the herd as long as in more favorable environments. Two sources of data were used to examine this effect. The Red Angus Association of America provided breeder and herd records for stayability on 120,871 cows from 229 breeders with each herd subsequently classified into 8 different environments (biomes). In order to measure length of productive life, a score for longevity was assigned to each cow as the age at which she calved her last calf. Data were analyzed in ASREML3.0 using a mixed model with milk EPD, metabolic weight EPD and biome class as fixed effects to predict cow longevity (length of productive life). The quadratic term of milk EPD2 was included in the model as well as an interaction between milk EPD2 and biome. The interaction term was significant (P<0.001) with regression coefficients of 0.01414, 0.01693, 0.01096, 0.010504, 0.002240, 0.017331, 0.019607 and 0.014834 for the eight biomes of California Division, Subtropical Division, Prairie Division, Eastern Great Plains Division, Western Great Plains Division, Dry Domain, Rocky Mountain Province, and Hot Continental Division, respectively. The positive coefficients indicated that as levels of milk EPD increased so would longevity; however, rates were different depending upon biome. A logistic regression was also performed using SAS 9.3 with stayability to 6 years of age (a binary outcome) as the dependent variable for milk EPD, milk EPD2, metabolic weight EPD and biome as fixed effects. An interaction term for biome with milk EPD, and biome with milk EPD2 was also included and was significant (P<0.0001). As milk EPD increased the probability of a cow remaining in the herd increased for all biomes quantified by odds ratios. The second source of data was provided by the Colorado State University John E. Rouse Beef Improvement Center (BIC). Using SAS 9.3, the regression of longevity on the linear and quadratic effect of cow's milk EPD as a main effect was conducted resulting in a regression coefficient of 0.1002. This positive regression coefficient suggested that for higher levels of milk EPD, the positive relationship between milk EPD and longevity increased. Logistic regressions were also conducted with the BIC data for the binary outcomes of stayability to 3 years of age and 6 years of age with those regressed on milk EPD and milk EPD2. The resulting regression coefficient for stayability of 3 years was -0.0537 with an odds ratio of 0.948. For stayability to 6 years, the resulting regression coefficient was -0.0354 with an odds ratio of 0.965. These results suggested very little change in odds for receiving a stayability score of 1 as milk increases. Based on our results from the data from RAAA, we would reject our hypothesis that in areas of forage restriction that cows with higher milk EPD would not remain in the herd as long as those in environments with more abundant forage. According to the results from the BIC herd, we would also reject our hypothesis that cows with high milk EPD would have an increased probability of being culled from the herd.
Keywords: beef cattle; stayability; milk EPD; longevity